2006
DOI: 10.1145/1141911.1141959
|View full text |Cite
|
Sign up to set email alerts
|

Efficient simulation of large bodies of water by coupling two and three dimensional techniques

Abstract: Figure 1: Simulation of a wake behind a kinematically scripted boat (1500 × 300 horizontal resolution). AbstractWe present a new method for the efficient simulation of large bodies of water, especially effective when three-dimensional surface effects are important. Similar to a traditional two-dimensional height field approach, most of the water volume is represented by tall cells which are assumed to have linear pressure profiles. In order to avoid the limitations typically associated with a height field appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 53 publications
0
68
0
1
Order By: Relevance
“…Hybrid methods have been proposed to model both macroscopic and microscopic fluid phenomena in one scene. Irving et al [2006] coupled 2D and 3D simulation techniques to model large quantities of water with surface details. Nobile [2009] proposed a two-way coupled method to simulate blood flow at various resolutions and tested the system using a very simplified model.…”
Section: Related Workmentioning
confidence: 99%
“…Hybrid methods have been proposed to model both macroscopic and microscopic fluid phenomena in one scene. Irving et al [2006] coupled 2D and 3D simulation techniques to model large quantities of water with surface details. Nobile [2009] proposed a two-way coupled method to simulate blood flow at various resolutions and tested the system using a very simplified model.…”
Section: Related Workmentioning
confidence: 99%
“…Although the simplest schemes trace back along straight line characteristics and use low order interpolation to estimate the data, one can trace back arbitrarily high order curved characteristics and use arbitrarily high order interpolation, see for example [38]. The simplicity of these schemes makes them quite useful for adaptive grids and other data structures, see for example [7,31,30,47,16]. Recently, authors have considered using semi-Lagrangian methods as building blocks in other schemes, for example [17,18,6] showed that the second order accurate BFECC method of [5] can be made unconditionally stable using the first order accurate semiLagrangian method as a building block.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many methods have been developed to visualize fluids realistically simulations; however, the computational cost of these methods have always been high [1] [2]. With the recent developments of techniques for obtaining faster simulations using high performance-computers, it has now become possible to calculate fluid simulations in real time.…”
Section: Introductionmentioning
confidence: 99%